2010
DOI: 10.1590/s1413-70542010000400002
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação de dejeto suíno e estrutura de um latossolo vermelho sob semeadura direta

Abstract: RESUMOObjetivou-se, neste trabalho, estimar o efeito da aplicação de doses crescentes de dejetos suínos, em atributos físicos do solo. O experimento localizado em Campos Novos, SC, foi conduzido num Latossolo Vermelho Distroférrico, no delineamento experimental em blocos casualizados, com quatro repetições, com os tratamentos: testemunha (0); adubo solúvel (AS); combinação dejeto e adubo solúvel (DS); dejeto líquido suíno aplicado nas doses de 50, 100 e 200 m 3 ha -1 . Desde 2001 foi cultivado milho e aveia pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
26
2
12

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 10 publications
10
26
2
12
Order By: Relevance
“…However, differences among treatments were observed for water retention in pores less than 50 µm in diameter, saturated hydraulic conductivity, and arithmetic mean diameter of air-dried aggregates (Table 3). Similar results have been reported in other studies comparing physical characteristics of plots to which different rates of pig slurry were applied (Veiga et al, 2008;Arruda et al, 2010;Veiga et al, 2012).…”
Section: Soil Physical Propertiessupporting
confidence: 89%
See 2 more Smart Citations
“…However, differences among treatments were observed for water retention in pores less than 50 µm in diameter, saturated hydraulic conductivity, and arithmetic mean diameter of air-dried aggregates (Table 3). Similar results have been reported in other studies comparing physical characteristics of plots to which different rates of pig slurry were applied (Veiga et al, 2008;Arruda et al, 2010;Veiga et al, 2012).…”
Section: Soil Physical Propertiessupporting
confidence: 89%
“…Bulk density is lower in the 0.00-0.05 m layer, increasing with depth. Similar results were obtained by Arruda et al (2010), who also examined the effect of pig slurry application on soil physical properties. These authors concluded that the lower density in surface layers could be related to the organic matter introduced when organic residues are applied, which may improve the degree of aggregation and reduce the soil mass by lowering specific density, and may even fill soil pores.…”
Section: Soil Physical Propertiessupporting
confidence: 83%
See 1 more Smart Citation
“…A reduction of the amounts of water-stable aggregates retained on the sieve of 8.00-4.76 mm for UWC rates above 50 m 3 ha -1 (second year of assessment) was also observed with application of high rates of other organic sources, such as alkaline residues from the pulp and paper industry (Medeiros et al, 2009), pig slurry (Arruda et al, 2010), vinasse from sugarcane (Passarin et al, 2007), and turkey litter (Costa et al, 2008;Pinto et al,. 2012).…”
Section: Resultsmentioning
confidence: 84%
“…The authors reported increased aggregation with 2.6 Mg ha -1 and dispersing effect of the chemical elements when higher rates were applied (10.5 Mg ha -1 ). Arruda et al (2010) observed that the aggregate stability in an Oxisol was higher in the control treatment (GMD = 6.1 mm) and decreased with the application of 50 and 100 m 3 ha -1 of pig slurry (GMD = 5.7 mm). Also, Oades (1984) observed that organic acids can exert direct dispersing effects or aggregate complexation by cations such as Al 3+ .…”
Section: Resultsmentioning
confidence: 88%